COVID-19 Outbreak: Activating Congruous Internal Marketing Communication Strategies - Goyal, Mukta; Srivastava, Abhishek (Ushus Journal of Business Management, 2021)
The COVID-19 pandemic is a disaster situation unlike any other that we have seen in living memory, impacting virtually any company across the globe. In a time like this, it is crucial for the organization to make internal relations a priority. In doing so, you need to ensure that your administrators use the best resources to keep staff well informed, which will give the company a greater chance to stay on track and keep your people safe. With a deeper understanding in connection with lockdown scenario in the period of COVID-19, many new and abnormal solutions turns into new normal. However, with loads of problems, somehow together we have now managed to turn our business with new dealings followed by varied mysteries. Undoubtedly, we are now turning into a noble mechanism as to drive in the direction of finding conclusive and ground-breaking results for the mass concerns in association with Internal Marketing Communications. For business leaders, their public response to the challenges of lockdown, furlough and staff health and safety were fundamental in determining public opinion of the brand, with a clear knock-on effect to customer loyalty and sales. Despite of challenges faced by organisations which are unparalleled to the existing scenario and can pretend like devastating effect in the pandemic situation, here in this paper, researchers have tried to drag the concepts of disruption of services with different prominent organisations in connection with the management of sales along with the requirements to manage workforce to induce them to operate remotely and off-course in analysing situations. Researchers have also focused on the issues like health & welfare of workforces and providing significant contribution to the society as well. In the face of a crippling pandemic, technology has emerged as a major lifesaver. Communication is a major key to our interconnected existence and technology is the driving force that maintains our connections.